THE IMPORTANCE OF EDUCATING THE ENTREPRENEURSHIP OF PRESCHOOL CHILDREN (TAMADDUN NURI JURNALI, 2024)
This article examines the importance of nurturing initiative in preschool children and emphasizes its decisive role in their overall formation. Through a comprehensive review of the literature, it examines the various methods used to promote initiative and examines their effectiveness. The study presents empirical findings that illuminate the outcomes of preschool initiatives and discusses implications for educators, parents, and the public.